Isoglosses Boundary in a Language Mapping of Malay-Riau Language: A Dialectology Case - Vina Fathira (J-SHMIC : Journal of English for Academic, 2018)
Dialectology is a part of sociolinguistics that is known as regional dialect topic. To ease the readers to understand the regional dialect especially in language mapping for certain region, the researcher used isoglosses boundary. Isoglosses boundary is the line that separate between region of having different etyma. The aim of this research is to elaborate the language mapping in dialectolgy by isoglosses boundary. Method of the research used qualitative method explained descriptively. In this research, the researcher conducted a dialectology research in Rokan Hulu Regency by 21 observation spots. In collecting data, there were 200 Swadesh words had been recorded, had been transcribed in phonetic transcription, and had been drawn in language mapping. The result showed that language mapping in Malay-Riau language was easy to analyze the differencess of language used by using isoglosses boundary. The languge mapping founds a language with some dialects used, Malay-Riau language with Bengkalis Minang dialect, with Mandailing dialect since the position of Rokan Hulu Regency lies among 3 regions having different in languages. They are West Sumatra Province with Minangese language, North Sumatra Province with Bataknese/Mandailing language, and Bengkalis Regency with Malay Riau Island language. The most dominant was Malay-Riau language, Malay-Riau language with Mandailing dialect. It means that, there is only one language used in Rokan Hulu Regency. It is called Malay-Riau language with Mandailing Dialect.